2021
DOI: 10.3389/fmicb.2021.631468
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Alterations in Shrimp Stomach During Acute Hepatopancreatic Necrosis Disease and Effects of Taurocholate on Vibrio parahaemolyticus

Abstract: Acute hepatopancreatic necrosis disease (AHPND), a recently emerged bacterial shrimp disease, has increased shrimp mortality and caused huge economic losses in many Asian countries. However, molecular factors underlying pathogenesis of this disease remain largely unknown. Our objective was to characterize metabolic alterations in shrimp stomach during AHPND and determine effects of taurocholate on AHPND-causing Vibrio parahaemolyticus. Based on metabolomics, pathways for lipid metabolism and for primary bile a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…The finding was consistent with the previous report that SP and ChyB had a significantly higher expression level in resistant shrimp line during the AHPND infection (Mai et al, 2021). Several studies have indicated that metabolic processes such as lipid metabolism and carbohydrate metabolic process in shrimp were greatly affected during AHPND infection (Velazquez-Lizarraga et al, 2019;Kumar et al, 2021). Taken together, the activated myosin, actin, and energy metabolism might indicate that the shrimp were healthier, which led to higher resistance of shrimp to disease.…”
Section: Discussionsupporting
confidence: 92%
“…The finding was consistent with the previous report that SP and ChyB had a significantly higher expression level in resistant shrimp line during the AHPND infection (Mai et al, 2021). Several studies have indicated that metabolic processes such as lipid metabolism and carbohydrate metabolic process in shrimp were greatly affected during AHPND infection (Velazquez-Lizarraga et al, 2019;Kumar et al, 2021). Taken together, the activated myosin, actin, and energy metabolism might indicate that the shrimp were healthier, which led to higher resistance of shrimp to disease.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have also reported that pathogenesis related mechanisms such as bacterial secretion, quorum sensing and biofilm formation were significantly induced in the gut of host infected by V. harveyi (Khan et al, 2020;Deng et al, 2020). Evidently, Vibrio infection in L. vannamei have been shown to cause minor to drastic alterations in various shrimp metabolic functions such as cell cycle, glycine, serine, threonine, cysteine, methionine, purine, pyrimidine, pyruvate, quorum sensing and lipid metabolism (Kumar et al, 2021;Alvariz-Ruiz et al, 2022). Therefore, based on this PICRUSt analysis, we hypothesize that 20 ppt may likely be one of the environmental stressors to V. harveyi, given that biofilm formation process was significantly higher in shrimp gut microbiota of 20VH.…”
Section: Discussionmentioning
confidence: 99%
“…24 On the other hand, levels of lipid metabolites (bile acid components taurocholate and taurochenodeoxycholate) were found decreased in the stomachs of AHPND strain V. parahaemolyticus-infected P. vannamei, which is believed to be a pathogen-induced phenomenon related to biofilm formation that is enhanced by taurocholic acid to allow the release of PirAB VP toxin to promote bacterial dispersion. 25 Similarly,…”
Section: Bacterial-induced Metabolic Changes In Crustaceansmentioning
confidence: 98%
“…parahaemolyticus ‐infected P . vannamei , which is believed to be a pathogen‐induced phenomenon related to biofilm formation that is enhanced by taurocholic acid to allow the release of PirAB VP toxin to promote bacterial dispersion 25 . Similarly, V .…”
Section: Changes In Host Metabolomementioning
confidence: 99%